A Retrospective 10-Year Analysis of Water Absorbent Bead Ingestion in Children - Feride Mehmetoğlu (Emergency Medicine International)
Aim. This retrospective case series was designed to evaluate the clinical experience of pediatric patients who had ingested water absorbent beads (WABs) and review the relevant literature. Materials and Methods. A retrospective chart analysis of 21 children who were admitted to the emergency service or outpatient clinic with complaints of swallowing WABs during a 10-year period was performed. The patients were divided into two groups: 6 patients who were hospitalized and 15 patients who were observed as outpatients for groups 1 and 2, respectively. All data were screened with respect to presentation, age, gender, clinical and radiological findings, modalities of treatment, and follow-up. Results. All patients were asymptomatic with uneventful outcomes. Laboratory studies, X-ray, and ultrasound examinations revealed normal results. None of the patients underwent surgery or other medical procedures. Gastrointestinal system obstruction or any other pathological findings were not detected after WAB ingestion. No complications were identified during follow-up. Discussion. This first clinical study showed that asymptomatic patients do not require inpatient observation and laboratory investigations, X-ray, and ultrasound. However, results of the present study cannot be generalized to children of all ages due to the few cases of bowel obstruction reported to date in small children.